2003
DOI: 10.1002/eji.200323287
|View full text |Cite
|
Sign up to set email alerts
|

Role of T cell help and endoplasmic reticulum targeting in protective CTL response against influenza virus

Abstract: We report on the induction of primary and long-term memory cytotoxic T lymphocyte (CTL) responses against the nucleoprotein of the influenza virus A/PR8/34 in mice immunized with plasmid DNA targeted to B lymphocytes in the spleen. We found that the magnitude of the CTL response and the size of the pool of memory CTL was greater when the CTL response was induced in presence of T cell help. Interestingly, immunization with a signal sequencecompetent transgene was markedly superior to immunization with a transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 53 publications
2
26
0
Order By: Relevance
“…This finding is consistent with the fact that lymphoma cell transfectants process and present to T cells peptides of endogenously synthesized Ig variable region via both MHC class II or class I pathways (22,23). When plasmid DNA coding for an Ig heavy chain gene controlled by the Ig promoter is injected into the spleen of adult mice, production of antibodies and activation of T cell responses against heterologous epitopes expressed in the variable region are readily induced (24,25).…”
supporting
confidence: 65%
See 2 more Smart Citations
“…This finding is consistent with the fact that lymphoma cell transfectants process and present to T cells peptides of endogenously synthesized Ig variable region via both MHC class II or class I pathways (22,23). When plasmid DNA coding for an Ig heavy chain gene controlled by the Ig promoter is injected into the spleen of adult mice, production of antibodies and activation of T cell responses against heterologous epitopes expressed in the variable region are readily induced (24,25).…”
supporting
confidence: 65%
“…Plasmid ␥1NANP, ␥1NV 2 NA 3 , and ␥1NV 2 NP 3 were engineered as described (25,29). The gene for enhanced GFP (EGFP) was inserted at the C terminus of the human ␥1 constant region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At variance with these in vivo studies are experiments from this laboratory showing that genetically programmed B lymphocytes can serve as the APC to prime anti-viral CD8 T cell responses. Importantly, we showed that CD8 T cell priming in vivo occurs in relB (-/-) mice that lack functional DC [17,18], raising the possibility that B lymphocytes that process endogenously synthesized antigen prime CD8 T cells directly. In the course of these studies we also showed that heightened protection against lethal virus challenge, and synchronization of a protective CTL response, require CD4 T cell help.…”
Section: Introductionmentioning
confidence: 94%
“…After 5 days [ 3 H]thymidine (1 lCi/well) was added, the cells incubated for additional [16][17][18] h and the radioactivity measured in a Betaplate (Wallac, Turku, Finland). In additional CD8 T cell priming experiments, B lymphocytes transgenic for c1OVA 323-339 and c1OVA 257-264 together (cotransfection) or separately (independent transfection) were cultured with 2Â10 5 OVA-specific TCR-transgenic CD4 T cells and 2Â10 5 OVA-specific TCR-transgenic CD8 T cells in a 96 well plate for 2, 4 or 6 days.…”
Section: In Vitro Culturesmentioning
confidence: 99%